2011
DOI: 10.1016/j.ejcts.2010.09.048
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of surgical and interventional therapy of native and recurrent aortic coarctation regarding different age groups during childhood

Abstract: The current strategy of an age-related therapy for native and recurrent aortic coarctation in our institution is surgery in infants <6 months (group A), either surgery or balloon dilatation in younger patients <6 years (group B), while in older children >6 years of age (group C) the trans-catheter treatment with stent implantation is an excellent alternative to surgery. Balloon dilatations showed limited results with an overall re-intervention rate of 53% and, therefore, should mainly be performed as a rescue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 27 publications
1
43
0
3
Order By: Relevance
“…[8] Surgical techniques include simple endto-end anastomosis, extended end-to-end anastomosis, patch plasty, and graft interposition. Albeit none of the techniques used for aortic coarctation repair today was proved to be superior to the other, [9] our study showed significant statistical difference between surgical techniques regarding mortality. Patients who underwent extended end-to-end anastomosis had the highest mortality rate when compared to other techniques (Table 4).…”
Section: Discussionmentioning
confidence: 52%
“…[8] Surgical techniques include simple endto-end anastomosis, extended end-to-end anastomosis, patch plasty, and graft interposition. Albeit none of the techniques used for aortic coarctation repair today was proved to be superior to the other, [9] our study showed significant statistical difference between surgical techniques regarding mortality. Patients who underwent extended end-to-end anastomosis had the highest mortality rate when compared to other techniques (Table 4).…”
Section: Discussionmentioning
confidence: 52%
“…[146][147][148][149][150][151][152][153] It is particularly useful for evaluation of the aortic arch after endovascular intervention (stent or stent graft) where aneurysm, aortic wall injury or recurrent arch obstruction are relatively common. [154][155][156][157][158][159] It is recommended that every patient with repaired or unrepaired aortic coarctation have comprehensive evaluation of the thoracic aorta, and that those who have undergone intervention should undergo serial evaluation by cardiovascular CT or CMR throughout adulthood. 23 Cardiovascular CT may be considered the optimal diagnostic modality for evaluation of suspected vascular rings and slings, and for assessment of vascular anatomy and associated tracheobronchial narrowing.…”
Section: Patientsmentioning
confidence: 99%
“…Abb. 9) hat gegenüber der reinen Ballondilatation den Vorteil, dass die Stenose praktisch ohne Restgradienten aufgeweitet wird [20]. Zudem ist das Dissektions-(und Ruptur-)Risiko bei der Aufweitung mit Stent geringer als bei der alleinigen Ballondilatation.…”
Section: Aortenisthmusstenoseunclassified